Pengaruh Customer Value terhadap Brand Loyalty: Customer Satisfaction sebagai Variabel Intervening pada Produk Smartphone Samsung di Kota Sampit - Marpuah, Marpuah; Andriyati, Yuli (Keizai, 2020)
This study aims to know the effect of customer value on brand loyalty with customer satisfaction as an intervening variable on Samsung smartphone products in Sampit city. This study uses a purposive sampling technique with 80 respondents in Samsung smartphone users. Data was collected through questionnaires and methods for data analysis performed using structural equation modeling (SEM). The result showed that: (1) the customer value has a positive effect on customer satisfaction, (2) the customer value has a positive effect on brand loyalty, and (3) customer satisfaction has no effect on brand loyalty, so it is concluded that customer satisfaction is not an intervening variable between customer value and brand loyalty.